A Comprehensive Systematic Review of Diagnostic Approaches in Acute Appendicitis: A Comparative Analysis - Jeremy Stephen Hermanto; Andrew Theodorous Timothy; Mellvin Telasman (The International Journal of Medical Science and Health Research, 2026)
Introduction: Acute appendicitis is one of the most common surgical emergencies worldwide. Despite its frequency, accurate diagnosis remains challenging due to atypical presentations, leading to high rates of negative appendectomy and missed diagnoses. A wide array of diagnostic tools exists, including clinical scoring systems, laboratory biomarkers, and imaging modalities such as ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI). However, there is significant heterogeneity in their reported accuracy, and an optimal, context-specific diagnostic pathway is still debated. This systematic review aimed to comprehensively compare the diagnostic performance of all available approaches and synthesize evidence to guide clinical decision-making. Methods: A systematic review was conducted following a predefined protocol. Electronic databases were searched for studies published up to 2025. Eligibility criteria included original research (RCTs, cohort studies, diagnostic accuracy studies) involving patients with suspected acute appendicitis that evaluated at least one diagnostic method and reported sufficient data to calculate performance metrics. Data on diagnostic methods, study population, reference standard, performance metrics (sensitivity, specificity, AUC), and moderating factors were extracted. Methodological quality was assessed. Results: Eighty studies were included. CT demonstrated the highest and most consistent diagnostic accuracy across populations, with pooled sensitivity of 94–97% and specificity of 94–98%. Low-dose CT protocols provided comparable accuracy to standard-dose CT while reducing radiation exposure by approximately 78% (Yoon et al., 2018; Sippola et al., 2020). Ultrasound performance was highly variable (sensitivity 55–97%), heavily dependent on operator expertise and patient selection. Emergency physician-performed point-of-care ultrasound (POCUS) showed excellent performance, particularly in pediatrics (Miller et al., 2025). MRI was highly accurate (sensitivity 92–96%, specificity 97–98%), especially in pregnant women (Kave et al., 2019; D'Souza et al., 2021). Among clinical scores, the Appendicitis Inflammatory Response (AIR) score outperformed the Alvarado score (Andersson & Stark, 2025), while the RIPASA score had high sensitivity but low specificity (Favara et al., 2022). The neutrophil-to-lymphocyte ratio (NLR) emerged as a promising biomarker, with a cut-off >4.7 showing good diagnostic accuracy (Hajibandeh et al., 2019). Discussion: The diagnostic performance of any tool is not absolute but is significantly moderated by clinical context, patient factors, technical protocols, and operator skill. CT remains the gold standard imaging modality for most adults, but its use must be balanced against radiation risk. Ultrasound is the recommended first-line imaging in children and pregnant women, with MRI as an excellent second-line option. Clinical scores and biomarkers are most valuable in resource-limited settings or as part of integrated algorithms. The review reconciles apparent contradictions in the literature by highlighting these moderating factors. Conclusion: No single diagnostic approach is universally superior. An integrated, context-specific framework is recommended: CT (preferably low-dose) for typical adults; US first-line for children, with selective CT/MRI; MRI for pregnant women; and clinical scores (AIR) combined with biomarkers (NLR, WBC/CRP) in resource-limited settings. Future research should focus on validating AI tools, standardizing ultrasound training, and evaluating cost-effectiveness of tailored pathways.